Step 1) Solve the first equation for #x#:
#x - y = 3#
#x - y + color(red)(y) = 3 + color(red)(y)#
#x - 0 = 3 + y#
#x = 3 + y#
Step 2) Substitute #3 + y# for #x# in the second equation and solve for #y#:
#2x + 2y = 2# becomes:
#2(3 + y) + 2y = 2#
#(2 * 3) + (2 * y) + 2y = 2#
#6 + 2y + 2y = 2#
#6 + (2 + 2)y = 2#
#6 + 4y = 2#
#-color(red)(6) + 6 + 4y = -color(red)(6) + 2#
#0 + 4y = -4#
#4y = -4#
#(4y)/color(red)(4) = -4/color(red)(4)#
#(color(red)(cancel(color(black)(4)))y)/cancel(color(red)(4)) = -1#
#y = -1#
Step 3) Substitute #-1# for #y# in the solution to the first equation at the end of Step 1 and calculate #x#:
#x = 3 + y# becomes:
#x = 3 + (-1)#
#x = 3 - 1#
#x = 2#
The solution is: #x = 2# and #y = -1# or #(2, -1)#